The role of uromodulin in cardiovascular disease: a review - Chen, Chengqian; Zhong, Wentao; Zheng, Hao; Dai, Gaoying; Zhao, Wei; Wang, Yushi; Dong, Qi; Shen, Botao (Frontiers in Cardiovascular Medicine, 2024)
Uromodulin, also referred to as Tamm Horsfall protein (THP), is a renal protein exclusively synthesized by the kidneys and represents the predominant urinary protein under normal physiological conditions. It assumes a pivotal role within the renal system, contributing not only to ion transport and immune modulation but also serving as a critical factor in the prevention of urinary tract infections and kidney stone formation. Emerging evidence indicates that uromodulin may serve as a potential biomarker extending beyond renal function. Recent clinical investigations and Mendelian randomization studies have unveiled a discernible association between urinary regulatory protein levels and cardiovascular events and mortality. This review primarily delineates the intricate relationship between uromodulin and cardiovascular disease, elucidates its predictive utility as a novel biomarker for cardiovascular events, and delves into its involvement in various physiological and pathophysiological facets of the cardiovascular system, incorporating recent advancements in corresponding genetics.